Arkansas Archaeology. Essays in Honor of Dan and Phyllis Morse, edited by Robert C. Mainfort and Marvin D. Jeter, Fayetteville, University of Arkansas Press, 1999 - Dunnell, Robert C. (Bulletin of the History of Archaeology, 2000)
This collection of ten essays honors the retirement of Dan and Phyllis Morse from the Northeast Regional Office of the Arkansas Archeological Survey and the University of Arkansas system. A brief recounting of the honorees' professional lives is the subject of a well-written essay by Mary Kwas accompanied by a "selected" bibliography and a short collection of anecdotes. An environmental account of the central Mississippi valley from 16,000 BP to 1000 BP (radiocarbon or calendric is significant but not stated) by Paul and Hazel Delcourt and the late Roger Saucier follows. Constructed around Saucier's 1994 mapped reconstructions of hydrology/geology, it is fleshed out by paleovegetation derived from eleven sites in the region, four new (but not described here). The Holocene central valley is as well known now as any area south of the glacial border.